2019
DOI: 10.1038/s41419-019-2154-4
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of miR-1205 and E2F1 modulates progression of laryngeal squamous cell carcinoma

Abstract: The burgeoning functions of many microRNAs (miRs) have been well study in cancer. However, the level and function of miR-1205 in laryngeal squamous cell cancer remains unknown. In the current research, we validated that miR-1205 was notably downregulated in human laryngeal squamous cell carcinoma (LSCC) samples in comparison with tissues adjacent to LSCC, and correlated with T stage, lymph node metastasis, and clinical stage. Using Kaplan–Meier analysis indicates that high expression of miR-1205 has a favorabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…16,17 By directly decreasing suppressor of cytokine signaling 2 (SOCS2) expression, miR-196b can increase the invasive and proliferative ability of LSCC cells while suppressing apoptosis, 18 whereas high levels of miR-1205 inhibit the growth, migratory, and invasive abilities of LSCC cells. 19 These findings suggest that miRNAs play an important role in the progression of LSCC.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…16,17 By directly decreasing suppressor of cytokine signaling 2 (SOCS2) expression, miR-196b can increase the invasive and proliferative ability of LSCC cells while suppressing apoptosis, 18 whereas high levels of miR-1205 inhibit the growth, migratory, and invasive abilities of LSCC cells. 19 These findings suggest that miRNAs play an important role in the progression of LSCC.…”
Section: Introductionmentioning
confidence: 90%
“…Understanding the mechanism of LSCC progression, invasion, and metastasis, as well as identifying more reliable biomarkers, is therefore critical for LSCC diagnosis and treatment. miRNAs are non-coding endogenous RNA molecules made up of [18][19][20][21][22] nucleotides that primarily dock the 3 0 untranslated region (UTR) of a target mRNA, causing degeneration or translation suppression. 13 miRNAs have been implicated in the pathogenesis of various tumors, as well as regulating cell proliferation, invasion, migration, chemoresistance, and angiogenesis, via multiple signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…19 Recently, miR-1205 has been reported as a tumor suppressor that is significantly downregulated in multiple cancer types. 20,21 In our study, E2F1 was predicted as the candidate target gene of miR-1205 by miRDB and Targetscan and was further testified by dual-luciferase reporter assay. Recently, a few studies have implicated that overexpression of E2F1 accelerates formation of various tumors.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, a multiscale integrated analysis revealed that E2F1 showed excellent diagnostic and prognostic values, which may be a potential regulator in esophageal cancer [ 10 ]. Interestingly, E2F1 has been identified to bind to microRNA (miR)-1205 promoter and transcriptionally inhibit miR-1205 expression in laryngeal SCC [ 11 ]. Therefore, we wondered whether E2F1 serves as a transcription factor to repress the transcription levels of miRNAs in ESCC.…”
Section: Introductionmentioning
confidence: 99%